Outdoor Testing of a Zig-Zag Solar Air heater with and without Artificial Roughness on Absorber Plate - Mahmoud Maustafa Mahdi; Ameer Abed Gaddoa (Journal of Engineering, 2019)
In this paper, thermal performance of a zig-zig solar air heater (ZZSAH) with and without using steel wire mesh on the absorber plate of the collector is experimentally investigated. The experimental work includes four inclination angles of the collector 20o, 30o, 45o, and 60o and four air mass flow rates of 0.03, 0.04, 0.06, and 0.08 kg/s under varieties of operating conditions of a geographic location of  Baghdad. New correlation equations of Nusselt number are obtained from experimental results for both types of collectors where the effect of varying of the inclination angle of collector taken into consideration in the experiment. The correlations show good agreement with the present experimental data. In addition, the effects of mass flow rate and temperature rise across the efficiency of collector air heater are investigated. The results reveal that the efficiency of (ZZSAH) at 45o inclination angle reaches the highest values among other degrees of inclination angles for both types of collectors under study. The results also show that the addition of wire mesh magnifies the effect of inclination angle.